2014
DOI: 10.1038/sc.2014.181
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of traumatic spinal cord injury in Denmark, 1990–2012: a hospital-based study

Abstract: Study design: Hospital-based incidence study. Objectives: To assess the incidence of traumatic spinal cord injuries (TSCIs) and TSCI incidence trends in relation to cause, age, gender, level and completeness of injury. Setting: Spinal Cord Injury Centre of Western Denmark. Methods: We reviewed medical records of TSCI patients admitted between 1 January 1990 and 31 December 2012. Proportions, incidence rates and incidence rate ratios were calculated for five time periods; 1990-94, 1995-99, 2000-04, 2005-09 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
26
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 16 publications
9
26
3
4
Order By: Relevance
“…We cite median age at onset for the purposes of this comparison – this was 37 years in 2000 [2] and was 49 years during 2010–2015. Our findings of an apparent increasing age at TSCI onset are similar to the findings reported in Western Denmark – mean age at onset was 47.5 years for 2010–2012 [13], Western ­Norway – mean age of onset was 48.9 years for 1997–2001 [16] and Scotland – mean age was 52.6 years for the period 2009–2013 [14]. …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We cite median age at onset for the purposes of this comparison – this was 37 years in 2000 [2] and was 49 years during 2010–2015. Our findings of an apparent increasing age at TSCI onset are similar to the findings reported in Western Denmark – mean age at onset was 47.5 years for 2010–2012 [13], Western ­Norway – mean age of onset was 48.9 years for 1997–2001 [16] and Scotland – mean age was 52.6 years for the period 2009–2013 [14]. …”
Section: Discussionsupporting
confidence: 80%
“…It is most appropriate that we compare this study with other retrospective studies, but we should emphasize that the time periods of data collection are not exactly the same in all studies. Compared to the most recent time periods reported in other studies, the mean crude incidence rate of 12.6 per million, as reported by our study, is greater than that reported in Western Denmark, 8.3 per million in the 2010–2012 period [13] but less than Scotland, 17 per million for 2009–2013 [14] or Iceland, 33.5 per million during 2005 to 2009 [15]. …”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…It is interesting that the number of transport-related injuries is stable or decreasing in developed countries (Cripps et al, 2014) due to prevention strategies, whereas fall-related injuries are increasing (van den Berg et al, 2010;Noe, 2015) over time due mainly to ageing problems.…”
Section: Discussionmentioning
confidence: 99%
“…The patients' experiences are considered to form an appropriate data source in ensuring sufficient richness for the present analysis. 30 In terms of age, gender, level and completeness of injury the participants reflect the epidemiological data on TSCI in Denmark, 31 further they had different background and education. We used a semi-structured interview guide with open questions, which invited the patients to address positive as well negative aspect of returning home.…”
Section: Discussionmentioning
confidence: 99%